Hybrid Structure Optimization of a PMSM Using Global and Local Methods for Higher Torque and Lower Volume - Ruzbehi, Shabnam; Hahn, Ingo (11th IEEE International Conference on Renewable Energy Research and Applications, ICRERA 2022, 2022)
In this work, a Structure Optimization procedure of a permanent magnet synchronous motor is shown, based on a hybrid method to gain a lower weight structure, lower torque ripple and cogging torque, and to preserve the torque as high as possible. As structure optimization is faced with a highly complex structure, to overcome this drawback a hybrid optimization method using a global and a local method is suggested. This hybrid method not only gains a smoother structure but also gains better technical results with considerable reduction of calculation time compared to non-hybrid simple optimization. The proposed hybrid method validity is approved on the rotor and permanent magnet (PM) part of a permanent magnet synchronous motor. The results lead to material and cost reduction, from another side to an improvement of the flux linkages and back-EMF waveforms. Also, torque ripple and cogging torque reduction lead to lower vibration and acoustic noise.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Genetic algorithms; PMSM; Sensitivity method; Topology optimization; Torque; Torque ripple